Two decades of research on natural products chemistry from Brazilian biodiversity: Inspirations and motivations - Da Silva Bolzani, Vanderlan [UNESP] (American Chemical Society (ACS), 2015)
Although the author is a distinguished scientist and natural products researcher and has an impressive list of accomplishments to her name, achieving these was not easy. In recounting her journey, she describes the hurdles that not only she had to overcome, but all women scientists, both in Brazil and in the scientific community around the world, must overcome. While society has progressed significantly over the last century to include more women in the scientific community and other professions, disparities still persist. The author provides strong insight into these disparities and what might be considered a sobering reality of the progress that has been made. However, in reflecting upon her own progress over the course of her career, she has proven that with enough passion and dedication, it is never impossible to achieve one's dreams.